MENGHAMBAT PERTUMBUHAN BAKTERI DENGAN EKSTRAK SIRIH (Piper betle Linn) DAN POTENSI PENGGUNAANNYA DALAM PENGAWETAN IKAN - Jabarsyah, Abdul (Jurnal Harpodon Borneo, 2014)
The purpose of this work was to observe the effect the extracts of Piper betle Linn on the growth of bakteri. The work was conduted on September to October 2012.  The extract of Piper betle  Linnwas 20 ppt, 40 ppt, 60 ppt, and 80 ppt. The bacteria used was (Vibrio sp). Bacteria cultured on Tryptic Soy Agar (TSA). The growth bacteria observed on the media and data were analyzed statistically.The Results of this work showed the differences of concentration of extract of piper betle leaf affected the growth of bacteria. The growth of bacteria was lower on 80 ppt < 60 ppt < 40 ppt and 20 ppt respectively. The best concerntration the extract were between 80 ppt and 60 ppt base on the Ftest) and ttest (0.01 and 0.05).That the extract may  useful for fish preservation under cool condition.  Keyword : Piper betle leaf extract, bacteria